MANAJEMEN STRATEGIK LEMBAGA PENDIDIKAN ISLAM DALAM MENGHADAPI PERSAINGAN GLOBAL - M. Agung Rif’at Syauqi; Afifah Mumtazah (Universitas Islam Bunga Bangsa Cirebon, 2023)
Islamic educational institutions in Indonesia face mounting competitive pressures from both domestic and international arenas, yet many continue to operate without a coherent and systematic strategic management framework. This study investigates the application of strategic management principles within Islamic educational institutions as a means of sustaining institutional relevance and competitiveness in the global landscape. The study pursues three specific objectives: (1) to analyze the theoretical foundations of strategic management as applicable to Islamic educational institutions, (2) to examine the principal challenges confronting Islamic educational institutions in the global competitive environment, and (3) to construct a strategic management model that is both managerially rigorous and epistemologically grounded in Islamic values. Employing a systematic library research methodology, this study critically synthesized thirty-two peer-reviewed sources published between 2020 and 2025. The findings yield a strategic management model designated as Islamic Adaptive Strategic Management (IASM), comprising four interconnected dimensions: environmental scanning through Islamic wisdom, strategy formulation based on maqashid al-syariah, strategy implementation through transformational Islamic leadership, and strategic evaluation via shura-based feedback mechanisms. Practical implications for madrasah principals, Islamic university administrators, and educational policymakers are discussed.